Mating System among Provenances of Sclerocarya birrea (A. Rich.) Hochst. - Violet J. Msukwa; Chimuleke R. Y. Munthali; Betserai I. Nyoka; Edward Missanjo; Alice Muchugi; Clement Okia; Simon Kang’ethe; Herbert Jenya (International Journal of Forestry Research)
Mating system of a species is critically important both genetically and ecologically in developing plans for breeding and gene conservation. This study was conducted to assess twenty provenances of Sclerocarya birrea (A. Rich.) Hochst. planted in Malawi. The trial was assessed for mating system and sex ratio at eighteen years of age. The results revealed that the mating system in S. birrea occurred from selfing, insect, and wind-mediated pollination. There were no significant (P>0.05) differences on seed germination percentage among the three mating systems. The germination percentages were 47%, 44%, and 43% for insect, wind, and self-pollinations, respectively. This implies that the seeds were viable in all the three mating systems. Production of viable seed from selfed flowers ruled out the possibility of apomixes in S. birrea. Most frequent flower visitors were the orders Hymenoptera and Lepidoptera with peak visitation period being from 7:00 to 11:30 hours in the morning and then 15:30 to 18:00 hours in the afternoon (+2 GMT) when temperatures were cooler. There were significant (P<0.05) variations in sex ratio among the provenances. Five provenances (Marracuene, Magamba, Tanzania pooled, Ngundu, and Matebeleland South) did not deviate significantly from sex ratio equality. The other provenances showed male-biased sex ratios.